Biliary-duodenal anastomosis using magnetic compression following massive resection of small intestine due to strangulated ileus after living donor liver transplantation: a case report - Ryusuke Saito; Hiroyuki Tahara; Seiichi Shimizu; Masahiro Ohira; Kentaro Ide; Kohei Ishiyama; Tsuyoshi Kobayashi; Hideki Ohdan (Surgical Case Reports)
Abstract Background Despite the improvements of surgical techniques and postoperative management of patients with liver transplantation, biliary complications are one of the most common and important adverse events. We present a first case of choledochoduodenostomy using magnetic compression following a massive resection of the small intestine due to strangulated ileus after living donor liver transplantation. Case presentation The 54-year-old female patient had end-stage liver disease, secondary to liver cirrhosis, due to primary sclerosing cholangitis with ulcerative colitis. Five years earlier, she had received living donor liver transplantation using a left lobe graft, with resection of the extrahepatic bile duct and Roux-en-Y anastomosis. The patient experienced sudden onset of intense abdominal pain. An emergency surgery was performed, and the diagnosis was confirmed as strangulated ileus due to twisting of the mesentery. Resection of the massive small intestine, including choledochojejunostomy, was performed. Only 70 cm of the small intestine remained. She was transferred to our hospital with an external drainage tube from the biliary cavity and jejunostomy. We initiated total parenteral nutrition, and percutaneous transhepatic biliary drainage was established to treat the cholangitis. Computed tomography revealed that the biliary duct was close to the duodenum; hence, we planned magnetic compression anastomosis of the biliary duct and the duodenum. The daughter magnet was placed in the biliary drainage tube, and the parent magnet was positioned in the bulbus duodeni using a fiberscope. Anastomosis between the left hepatic duct and the duodenum was accomplished after 25 days, and the biliary drainage stent was placed over the anastomosis to prevent re-stenosis. Contributions to the successful withdrawal of parenteral nutrition were closure of the ileostomy in the adaptive period, preservation of the ileocecal valve, internal drainage of bile, and side-to-side anastomosis. Conclusions Choledochoduodenostomy with magnet compression could be a less invasive and safer method for treatment of biliary stricture that cannot be accessed by conventional surgery.